Comparative analysis of the implementation of Triple Helix Theory in Greece and Hungary and lessons learned from both cases' - Chrysanthi Balomenou; Aniko Kalman; Konstantinos Kolovos (European Regional Science Association (ERSA), 2014)
In the theoretical part of our paper focused on a) The role of the Knowledge / Universities as a leader of Technological change ? Knowledge transfer dynamics and its influence on Regional Development, b) the Entrepreneurship education: The role of the Entrepreneurial University, c) Knowledge Spillovers and regional Innovation System (RIS): empirical evidence of some European Regions, d) the current situation in Greek Higher Education, focusing on the New Educational Law and especially on the plan "Athena" of the Ministry of Education, for the restructure / reallocation of the Greek Universities and Technological Institutions e) The new Law for Research Technology and Innovation in Greece (Horizon 2020 program) c) The Hungarian case study. In the empirical part of our paper, we are studding the restructure / reallocation of the Greek Universities and Technological Institutions. Our research methodology, based on the data extracted from targeted questionnaires addressed both to Greek entrepreneurs and Greek universities ? Scientific Institutions, attempts to show on one hand how the Universities assess the business environment and their new role in the relevant new institutional framework and on the other hand how the Greek industries evaluate their cooperation with the universities sector and their new role in terms of supporting the local entrepreneurship, as well. The used method for analyzing the results is the one of SPSS (descriptive statistics, correlation ? convexity indicators). The main findings coming by the processing of the statistical data of our scientific research, reveal that in crisis period the universities can find a new source of funding by "advertising" their main mission, which is the diffusion of Knowledge, and especially, the innovative one that enterprises need, in order to succeed and to overcome the crisis bad effects. Thus, we can observe that the results of our empirical analysis are strongly related to the relevant literature presented in the theoretical part of our paper. Finally, considerable general conclusions, policy proposals and questions/ challenges for further research will be presented at the end of our study. Finally, we would like to draw your attention on the fact that during this period is taking palace an ongoing relevant research in Hungary and we are expecting the results in order to be able to make a comparative analysis and consequently the appropriate SWOT ANALYSIS.
Keywords: O30; O31; O32; O33; O38; R11; R58; 330; Universities; Triple Helix Theory; Local Entrepreneurship; Endogenous regional growth; cross country cooperation; collaboration in knowledge economy